2017
DOI: 10.1002/jsfa.8371
|View full text |Cite
|
Sign up to set email alerts
|

Is meat quality of forage‐fed steers comparable to the meat quality of conventional beef from concentrate‐fed bulls?

Abstract: The Conventional beef was better accepted by consumers than the beef from both forage-based systems because it was the most tender. Thus tenderness of meat from forage-fed steers should be improved to ensure consumer acceptance. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The application of alfalfa in the diets of meat-producing animals is controversial. On the one hand, alfalfa can improve the dry matter (DM) digestibility, increase the proportion of unsaturated fatty acids in meat, and reduce lipid peroxidation of meat . On the other hand, alfalfa can bring undesirable flavor substances into meat products .…”
Section: Introductionmentioning
confidence: 99%
“…The application of alfalfa in the diets of meat-producing animals is controversial. On the one hand, alfalfa can improve the dry matter (DM) digestibility, increase the proportion of unsaturated fatty acids in meat, and reduce lipid peroxidation of meat . On the other hand, alfalfa can bring undesirable flavor substances into meat products .…”
Section: Introductionmentioning
confidence: 99%
“…However, other factors such as diet could be taken into account, especially when it contains a high level of fat and high marbling scores in the meat [ 62 ]. Although Giaretta et al [ 63 ] observed a positive correlation between meat tenderness and fat content, in particular to intramuscular fat [ 64 , 65 ], other authors reported that the diet is probably not the major cause of tenderness differences [ 43 ]. These authors reported that the fatness scores of Retinta carcass showed lower subcutaneous fat thickness than other rustic breeds, and they had low intramuscular fat values (<2%) under different types of feeding, which could be a reason for thinking about the importance of exercise in the above diet.…”
Section: Resultsmentioning
confidence: 99%
“…However, the study by Van Elswyk & McNeill (2014) also highlighted issues associated with sensory quality as changing the fatty acid content of beef can influence colour, flavour, sensory attributes and shelf-life (Scollan et al, 2006). Steaks from pasture have been reported to be less tender than steaks from grain-finished beef (Blanco et al, 2017). In addition, the external fat of pasture-derived beef has been reported to be more yellow (a consequence of increased β-carotene in adipose tissue).…”
Section: Meat Product Quality From a Pasture-based Feeding Systemmentioning
confidence: 99%